Rapid prototyping fabrication of soft and oriented polyester scaffolds for axonal guidance. (August 2020) - Kaplan, Ben; Merdler, Uri; Szklanny, Ariel A.; Redenski, Idan; Guo, Shaowei; Bar-Mucha, Zemach; Michael, Noah; Levenberg, Shulamit
Abstract: Biodegradable polyesters have been extensively used for preparation of nerve guidance scaffolds, due to their high biocompatibility and defined degradation periods. However, conventional methods for fabrication of porous polyester scaffolds provide limited control over shape and micro-architecture. Here, a fabrication procedure based on 3D printing was developed to generate highly ordered and anatomically personalized, polyester scaffolds for soft tissue regeneration. Scaffolds composed of Poly-lactic-glycolic acid (PLGA) and poly-L-lactic acid (PLLA) were specifically customized for nerve injuries. This was obtained by using an oriented multi-layer printing pattern which established a linear structure in the fabricated scaffolds to match the aligned topography of nerve tissues. The oriented scaffold was shown to guide regenerating axons to linear conformations and support growth of induced pluripotent stem cell-derived neurons in vitro and in vivo in a model of spinal cord injury. The described scaffolds may advance the field of nerve regeneration. Furthermore, modifications could be integrated to generate soft implants for various types of tissues.